Just Jaime - Libenson, Terri (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2019)
At the end of seventh grade Jaime and Maya's friendship is tested when their priorities are divided. Jaime knows something is off with her friend group. They've started to exclude her and make fun of the way she dresses and the things she likes. At least she can count on her BFF, Maya, to have her back . . . right? Maya feels more and more annoyed with Jaime, who seems babyish compared to the other girls in their popular group. It's like she has nothing in common with Jai anymore. Are their days as BFFs numbered . . . ?
Ages 8-12.
Keywords: Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Middle schools -- Juvenile fiction; Best friends -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Middle schools -- Comic books, strips, etc; Best friends -- Fiction; Friendship -- Fiction; Schools -- Fiction; Graphic novels; Cartoons and comics; JUVENILE FICTION / Comics & Graphic Novels / Humorous; JUVENILE FICTION / Social Themes / Friendship; JUVENILE FICTION / Social Themes / Self-Esteem & Self-Reliance.; Best friends; Friendship; Middle schools; Middle school students -- Comic books, strips, etc; Middle schools -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Middle school students -- Fiction; Middle schools -- Fiction; School stories; Friendship -- Fiction; Comic books, strips, etc; Graphic novels; Comics (Graphic works); Fiction; Graphic novels; Juvenile works; Graphic novels; Comics (Graphic works); School stories; Graphic novels